1999
DOI: 10.1111/j.1834-7819.1999.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of methyl methacrylate from heat‐curved and autopolymerized resins: Cytotoxicity testing related to residual monomer

Abstract: Three heat-cured and three autopolymerized acrylic denture bases with different mixing proportions and/or processing methods were investigated for the amount of residual monomer content and methyl methacrylate (MMA) released into saliva after incubation during the first and second 24 hours after processing. A corresponding range of concentrations of MMA was also used to test for cell cytotoxicity using a culture of human oral fibroblasts. The results showed that the amount of residual monomer was dependent not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
136
0
21

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 22 publications
9
136
0
21
Order By: Relevance
“…Dessa forma, alguma quantidade de monômero, denominada monômero residual, está presente nesses materiais. Estudos indicam que quantidades variadas de MMA podem ser liberadas na cavidade bucal, durante o uso de aparelhos ortodônticos removíveis ou de trabalhos protéticos como placas oclusais, coroas e pontes provisórias 2,10 . Esse monômero residual pode, além de alterar as propriedades físicas finais das resinas 5,15 , quando em contato com a saliva e tecidos moles, levar ao aparecimento de reações teciduais locais e sistêmicas em alguns indivíduos 7,9,14 ( Fig.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Dessa forma, alguma quantidade de monômero, denominada monômero residual, está presente nesses materiais. Estudos indicam que quantidades variadas de MMA podem ser liberadas na cavidade bucal, durante o uso de aparelhos ortodônticos removíveis ou de trabalhos protéticos como placas oclusais, coroas e pontes provisórias 2,10 . Esse monômero residual pode, além de alterar as propriedades físicas finais das resinas 5,15 , quando em contato com a saliva e tecidos moles, levar ao aparecimento de reações teciduais locais e sistêmicas em alguns indivíduos 7,9,14 ( Fig.…”
Section: Introductionunclassified
“…Muitos trabalhos analisaram a liberação de MMA residual em diversos intervalos de tempo e constataram uma maior liberação em solução nas primeiras 24 horas 5,6,10,12 . Todavia, Koda et al 12 relataram maiores níveis de MMA residual após 7 dias, utilizando corpos-deFiGuRa 1 -Paciente em uso de aparelho ortodôntico removível.…”
Section: Introductionunclassified
“…3 Terjadinya monomer sisa dipengaruhi oleh perbandingan pencampuran antara bubuk dan cairan resin akrilik dari setiap jenis bahan dan prosedur prosesing resin akrilik. 14 Hasil suatu penelitian, menyimpulkan kandungan monomer sisa dari resin akrilik jenis rapid heat cured paling tinggi pada penggodokan 20 menit dan paling rendah pada penggodokan selama 40 menit. 5 Hal yang sama juga telah dilaporkan oleh peneliti lain, kandungan monomer sisa dari resin akrilik yang di proses selama 20 menit pada suhu 100° C paling tinggi dibandingkan yang diproses pada suhu tinggi dan waktu lama.…”
Section: Pembahasanunclassified
“…Hal ini akan berpengaruh terhadap kerusakan jaringan yang lebih besar. 19 Oleh karena itu metode yang digunakan untuk mengurangi substansi yang terlepas dari basis gigi tiruan yang baru diproses sebelum digunakan dalam rongga mulut, sebaiknya gigi tiruan direndam dalam air paling sedikit satu hari atau direndam dalam air panas suhu 50° C. 14,21 Hasil penelitian ini dapat disimpulkan tidak terjadi penurunan viabilitas sel fibroblast BHK-21 pada resin akrilik jenis rapid heat cured bila lama polimerisasi diperpanjang dari 20 menit.…”
Section: Pembahasanunclassified
“…[27][28][29][30] It has been reported that the acrylic resins used for the fabrication of denture bases have displayed various degrees of in vitro cytotoxicity and in vivo allergic responses, which have been probably caused by non-reacting components that remain after the polymerization process. [31] Nevertheless, studies about cytotoxic effect of polyamides are very limited.…”
Section: Cytotoxic Evaluation Of Polyamidementioning
confidence: 99%